2020
DOI: 10.1037/fsh0000524
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events and associations with child and family emotional and behavioral well-being in diverse immigrant and refugee populations.

Abstract: Objective: Although stressful life events (SLEs) have been suggested to be associated with child well-being, few studies have examined SLEs with child and family behavioral and emotional well-being, especially within diverse populations. The current study examined the associations between SLEs and child behavioral and emotional outcomes, in addition to family-level measures of well-being. Method: Children 5-7 years old and their families (n ϭ 150) from 6 racial and ethnic groups (n ϭ 25 each for African Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“… 54 , 56 Culturally diverse families may be at higher risk for stressful life events and should be given particular attention. 57 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 54 , 56 Culturally diverse families may be at higher risk for stressful life events and should be given particular attention. 57 …”
Section: Discussionmentioning
confidence: 99%
“…54,56 Culturally diverse families may be at higher risk for stressful life events and should be given particular attention. 57 Understanding and responding to a toddler's needs may be more difficult for parents who have a negative perception of their child's temperament. 43 In this regard, research has shown that parental perceptions of difficult temperament are related to greater parenting stress, lower mindful parenting, lower parenting sense of competence, and lower parenting efficacy.…”
mentioning
confidence: 99%
“…Adverse childhood experiences (ACEs) are psychosocial stressors and traumatic events occurring before the age of 18, such as (1) physical abuse, sexual abuse, or neglect; (2) parental mental illness, substance abuse, or incarceration; (3) exposure to domestic violence or crime; and (4) divorce or household dysfunction. [1][2][3] Prior research shows intergenerational associations between parental experience of ACEs and negative health outcomes in their children. [4][5][6][7] For example, studies have shown associations between parental experience of 1 or more ACEs and increased risk for overweight/obesity, cardiovascular disease, asthma, and poor overall health among their children.…”
Section: Introductionmentioning
confidence: 99%
“…Both support for PA and limiting sedentary activity had the following response options: 1 = "Strongly disagree"; 2 = "Somewhat disagree"; 3 = "Somewhat agree"; 4 = "Strongly agree." Modeling of PA48 was assessed through 4 questions from a prior scale48 asking parents during a typical week how often they(1) Encourage [child] to do physical activities or play sports; (2) provide transportation or walk with [child] to a place where he or Continued doi: 10.3122/jabfm.2022.220134R1 Parental ACEs and Child Weight 43 copyright. on 20 February 2023 by guest.…”
mentioning
confidence: 99%
“…Parental stress has been demonstrated as a key moderating factor in the impact of environmental stressors on children's mental and physical health. [25][26][27] The relationship between household chaos and parents' stress levels may look different in different families. Further, there is a reasonable amount of evidence for the relationship between parental stress and child weight-related outcomes, including BMI, 28,29 but in combination with the other variables, has not been considered.…”
Section: Introductionmentioning
confidence: 99%